Analisis Perbandingan Profitabilitas Sebelum dan Sesudah Akuisisi pada Perusahaan Non Keuangan Terdaftar Bursa Efek Indonesia - Putri Yulfhita Claraini; Fitra Dharma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the impact of acquisitions on the profitability of non-financial companies listed on the Indonesia Stock Exchange (IDX), using Return on Assets (ROA) and Net Profit Margin (NPM) indicators as the main proxies. This study uses a quantitative approach with descriptive analysis methods and paired t-tests on two years before and two years after the acquisition. The results showed that in the ROA indicator, there was no statistically significant difference before and after the acquisition, although there was a descriptive decrease in value. Meanwhile, in the NPM indicator, only one of the four combinations of observation years (T-2 vs T+2) shows a significant difference, and the direction of change shows a drastic decrease until it reaches a negative value. This finding indicates that acquisitions do not necessarily increase company profitability, and even tend to have a negative impact within two years after the acquisition. This may be due to the non-optimization of the post-acquisition integration process. This study emphasizes the importance of careful integration planning and implementation so that the expected synergy benefits from acquisitions can be achieved